Comparison of Support and Clothing Pressure Distribution in Japanese and Australian Maternity Support Garments (Journal of Fiber Bioengineering and Informatics, 2026)
During the middle and late stages of pregnancy, the foetus grows rapidly, and the movements of the expectant mother are restricted. Therefore, a method that can support a sagging abdomen to support movement and distribute the weight of the lower abdomen throughout the torso to reduce the burden on the lower back needs to be investigated. This study aimed to develop a maternity support garment (MSG) that would provide comfortable support for rapid abdominal changes during the later stages of pregnancy. Nine types of MSGs used in Japan and Australia were analysed in terms of their clothing pressure distribution with a pregnant mannequin. In addition, pressure sense was indexed by the sensory evaluation of Japanese nongravid women in their 20s and 30s, and clothing pressure values obtained via simulation were analysed. The clothing pressure distribution of Japanese MSG is either almost perfect or looser, and when used alone, the MSGs keep the abdomen warm, except when the attached belt is used. Conversely, the Australian MSG is used with three types of tightness recommended by maternity hospitals; however, when double-layered with soft and hard types, the soft type concentrates pressure on the abdomen, and even the single-layer hard type MSG was observed to have higher pressure than the tight-fit sensation. Although the Australian MSGs provide support rather than insulation, the pressure that they exert on the gravid abdomen can restrict the blood flow to the foetus. Therefore, a narrow belt was combined with a single MSG and measured. The overlapping angle of the narrow belt generated excessive clothing pressure on the back from the heavy abdomen, making $15^◦$ the most suitable. The Australian soft-type single-layer MSG provided a perfect fit of clothing pressure but proved inadequate for supporting the heavy abdomen. Therefore, combining a narrow belt yielded good results. It was found that the medium type of MSG was preferred either as a single or double layer according to the pregnant woman’s preference, rather than combined with the belt. These findings are expected to advance understanding of the effects of existing MSGs on the pregnant abdomen, thus propelling further development of MSGs.
Keywords: Pregnant mannequin; Maternity support garments; Clothing pressure; Pressure feeling